HASIL PEMERIKSAAN GENEXPERT PADA PASIEN YANG DICURIGAI TUBERKULOSIS DI RS TINGKAT II DR. SOEPRAOEN PADA TAHUN 2023 - Sankise Valensia S Putri; Tiwik Eriskawati (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2026)
Pulmonary tuberculosis is an infectious disease that continues to be a major public health problem worldwide. It is caused by Mycobacterium tuberculosis infection and remains the second leading cause of death from infectious diseases globally. According to the 2023 report from the Malang City Health Office, there were 17,010 suspected tuberculosis cases. Confirmed cases included 565 cases identified at primary health centers, 1,632 at hospitals, and 19 in correctional facilities. This study aimed to describe the GeneXpert examination results among suspected tuberculosis cases at Dr. Soepraoen Army Hospital (RST TK II Dr, Soepraoen), Malang. The study employed a descriptive cross-sectional design using the total sampling method. A total of 2,944 samples were examined. The findings showed that GeneXpert examinations were most frequently conducted among young adults (20–44 years), followed by middle adults (45–64 years). Based on gender, men constituted the majority, accounting for 58% of the study population, while women made up 42% of the cases. Regarding patients’ location of residence, Sukun District in Malang City had the highest number of patients who tested positive for tuberculosis by the GeneXpert examination. Overall, positive GeneXpert were most frequently observed among young adult and middle-age adults. In addition, the number of men with positive results was higher than that of women. Sukun District recorded the highest number of positive GeneXpert results at RST TK II Dr. Soepraoen. Keywords: GeneXpert, Mycobacterium tuberculosis, molecular rapid test, pulmonary tuberculosis DOI 10.35990/mk.v9n2.p186-196